2019
DOI: 10.1093/jmcb/mjz015
|View full text |Cite
|
Sign up to set email alerts
|

miR-145 improves metabolic inflammatory disease through multiple pathways

Abstract: Chronic inflammation plays a pivotal role in insulin resistance and type 2 diabetes, yet the mechanisms are not completely understood. Here, we demonstrated that serum LPS levels were significantly higher in newly diagnosed diabetic patients than in normal control. miR-145 level in peripheral blood mononuclear cells decreased in type 2 diabetics. LPS repressed the transcription of miR-143/145 cluster and decreased miR-145 levels. Attenuation of miR-145 activity by anti-miR-145 triggered liver inflammation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Studies reported the silencing of miR-145 associated with increased liver inflammation in mice. Likewise, the lentivirus-mediated miR-145 inhibited macrophage infiltration, ameliorated glucose metabolism, and weight loss ( 180 ). This target has been characterized as a tumor-suppressor miRNA, impacting cell growth ( 59 ), leading to Myc proto-oncogene downregulation ( 181 ).…”
Section: The Role Of Adipose Tissue Mirnas In Cancermentioning
confidence: 99%
“…Studies reported the silencing of miR-145 associated with increased liver inflammation in mice. Likewise, the lentivirus-mediated miR-145 inhibited macrophage infiltration, ameliorated glucose metabolism, and weight loss ( 180 ). This target has been characterized as a tumor-suppressor miRNA, impacting cell growth ( 59 ), leading to Myc proto-oncogene downregulation ( 181 ).…”
Section: The Role Of Adipose Tissue Mirnas In Cancermentioning
confidence: 99%
“…For example, Liu et al [26] reported that miR-145 directed with CASC9, and the inhibition of miR-145 promoted cell migration and invasion but inhibited cell apoptosis in nasopharyngeal carcinoma cells, which provided a novel therapy for the treatment of nasopharyngeal carcinoma. Furthermore, there are various researches showing a robust association between miR-145 and inflammation [29][30][31]. However, the role of miR-145 in the treatment of tanshinone II A to cervical cancer have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Adding methyl groups (-CH 3 ) to DNA is the progress of DNA methylation, which usually leads to transcriptional silencing. 36 [40][41][42][43][44][45][46] MiR-145-5p can also target and inhibit KLF5 expression. 47 51 Moreover,…”
Section: Methylationmentioning
confidence: 99%